Correlation between Physical Activity and Stress Response in Polygraph Tests - Beguin, Catherine; Gray, Jennifer; Hepper, Valentine; Hetz, Kristin; Markson, Ian (Journal of Advanced Student Sciences (JASS), 2014)
This study investigated whether active individuals would be able to better cheat a polygraph test by virtue of a more controlled heart and respiration rate and a lower stress response. The subjects were asked 25 questions, nine of which were control questions, and the remaining were more intrusive, personal questions. The stress response to each question was measured as the participant’s skin response (EDA), heart rate (ECG), and respiration rate. After recording the truthful answers to the questions previously asked via a questionnaire, the participants were separated into active and non-active groups based on their average minutes of exercise per week. The physiological responses to each question were compared to the subject’s baseline to find the magnitude of the response, and this data was then normalized. The mean of the normalized data for the respective groups were compared using unpaired t-tests. Although not statistically significant, the mean responses for lies were generally higher than the mean responses for truths. The data showed no conclusive or significant results, indicating that we can not, at this time, show that more physically active individuals are better able to cheat a polygraph test than more sedentary individuals.
An article that appeared in JASS, issue 2014
Keywords: GSR; EDA; activity; heart rate; polygraph test; exercise